HAKEKAT KEBAHAGIAN MENURUT MONTFORT DAN RELEVANSINYA DALAM KONTEKS GEREJA KATOLIK INDONESIA - Elfridus Cancang; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Lembaga Penelitian STKIP Widya Yuwana, 2022)
This study aims to explore the nature of happiness according to Montfort and its relevance in the context of the Indonesian Catholic Church. Happiness is often identified with living in comfort, being spared of pain and difficulties in life, and as the satisfaction that is enjoyed after the desires and ideals have been achieved. This general paradigm needs to be examined more deeply by using the scalpel of the nature of happiness according to Montfort. This study uses the library research method. This study has found that the essence of happiness according to Montfort is not something that one wishes to be achieved (abstract), but an attitude of responsibility to live life here and now in union with Christ. The relevance of Montfort's teachings in the context of the way in which the Indonesian Catholic Church might live religion can be seen in three important attitudes. First, experiencing happiness by loving the crosses of daily life. Second, achieving union with Christ by siding with the poor. Third, experiencing happiness in the midst of religious plurality in Indonesia.